THE COMMUNICATION STRATEGY OF RADIO BUKU THROUGH SOCIAL MEDIA TWITTER TO GAIN LISTENER - Fitria Ayuningtyas; Kencana Ariestyani Suryadi (Lingkar Studi Komunikasi (LISKI), 2018)
A book is a form of the oldest media, existing since the start of the written language. Book as one of the mass communication has significant roles in building the quality of the country. Therefore the quality of the books must be considered, books not only for entertaining and to inform but should be able to educate. As one of parts in mass communication, radio is the strongest mass communication. Radio can be accessed by a number of people simultaneously. Anyone can listen to the radio while doing another activity. Along with technology development, radio can be listened by streaming. One of the radio that using internet technology is Radio Buku. For literature review in this research, the researcher used the internet radio theory, broadcast program theory, Computer-Mediated Communication theory and the utilization of Twitter as communication media also communication strategy theory. In this research, the researcher used the qualitative methodology, the data collection by using the triangulation data. The result of this research indicated that communication strategy, in this case, twitter that used by Radio Buku can gain the listener properly.